Copper-induced inhibition of photosynthesis: limiting steps of in vivo copper chlorophyll formation in Scenedesmus quadricauda - Küpper, Hendrik; Šetlík, Ivan; Šetliková, Eva; Ferimazova, Naila; Spiller, Martin; Küpper, Frithjof C (Functional plant biology, 2003)
The in vivo substitution of Mg2+ in chlorophyll by heavy metals is an important damage mechanism in heavy metal-stressed plants that leads to an inhibition of photosynthesis. In photosynthetic organisms with LHC II antennae, the in vivo substitution of Mg2+ by Cu2+ occurs particularly readily under low irradiance with a dark phase - a phenomenon referred to as 'shade reaction'. In the present study the limiting steps of the shade reaction were investigated with synchronised cultures of the chlorococcal green alga Scenedesmus quadricauda (Turp.) Bréb. The rate of copper chlorophyll formation during shade reaction was shown to be controlled by several factors; firstly, in some phases of the cell cycle, especially at the end of the light period, Mg2+ in chlorophyll was not accessible to substitution. This pattern is likely to be caused by cell cycle-dependent changes in photosynthesis and thylakoid ultrastructure, which were published earlier and are reconsidered in the discussion of the present work. Secondly, prolonged culture in a medium containing 3 μM Cu2+ reversibly increased the resistance of the strain to Cu2+. Culturing without added Cu2+ lowered the threshold concentrations of various deleterious effects more than 10-fold within 8 months of de-adaptation. Adaptation to high Cu2+ levels is discussed in the context of studies of the regulation of metal transporter proteins. In addition, it was also observed that toxic Cu2+ levels impaired photosynthesis sooner than cell division.